The Pragmatic Implicature in The Political Discourse of Surakarta’s Special Region Proposal - Ibrahim, Amelia Indriani; Mau, Fitriyanti K.; Hajati, Rianty; Laingo, Sri Rahmawati M (Journal of Advance in Language, Literature, and Education, 2025)
Using a qualitative-descriptive method, data were collected from speeches, news articles, and public statements between January and May 2025. These texts were analyzed through the lens of Gricean pragmatics and humanism to uncover the implicit messages and values embedded in the discourse. The findings show that implicatures function to indirectly express claims of justice, cultural identity, and perceived inequality, while also serving as rhetorical strategies to avoid overt conflict. Using a qualitative-descriptive method, data were collected from speeches, news articles, and public statements between January and May 2025. These texts were analyzed through the lens of Gricean pragmatics and humanism to uncover the implicit messages and values embedded in the discourse. The findings show that implicatures function to indirectly express claims of justice, cultural identity, and perceived inequality, while also serving as rhetorical strategies to avoid overt conflict. From a humanistic perspective, the use of such language reflects deeper aspirations for dignity, recognition, and ethical communication. This paper concludes that understanding implicature is essential for interpreting political discourse and fostering mutual understanding in culturally diverse societies.